Reducing orthopaedic theatre exposure during the COVID-19 lockdown: does a shift towards virtual reality-based training offer a solution?. (4th March 2021) - Arshad, Adam; Zaveri, Amit; Atkinson, Henry
Perspective: Orthopaedic training in the United Kingdom has changed little from the Halstedian apprenticeship model of graduated responsibility, with the mantra "see one, do one, teach one". Whilst still relevant in surgical teaching, the current and ongoing disruption to surgical training secondary to the coronavirus disease 2019 (COVID-19) outbreak highlights the need for alternative methods of experiential surgical learning, which allow for the development of the knowledge, skills, and attitudes of orthopaedic surgeons, to be sought.